(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
Art exhibitions play an important role in developing and supporting art activities in Malaysia and are often used as platforms to showcase works of the visual arts to the public. The National Cultural Policy (NCP) (1971) had a profound impact on the development of the visual arts in Malaysia. This policy is the country’s official attempt to establish a Malaysian identity, especially in the arts. Indirectly, it also challenged the boundaries of the definition of art in terms of philosophy, sociology, and aesthetics, in the context of exhibition practices. This paper discusses two local art exhibitions-Towardsa Mystical Reality (TMR) (1974) and Rupa dan Jiwa (1979). This paper discusses both exhibitions in the contexts of the NCP, particularly by focusing on the aspect of (Malay) nativism, and through the introduction of new ideas and concepts with an intellectual component. Keywords: Malaysian modern art, visual arts, art exhibitions, National Cultural Policy, Towards a Mystical Reality, Rupa dan Jiwa